Ecologia populacional dos Amphipoda (Crustacea) dos fitais de Caiobá, Matinhos, Paraná, Brasil - Dubiaski-Silva,Janete (1995)
Spalial and temporal density distributions of Amphipoda from the phytals of Caiobá are described. Air temperature oscillated from 16ºC (August and May) to 23ºC (March), surface water temperature from 17ºC (August) to 25ºC (March) and the salinity from 29.3 (May) to 32.8 (August). Two samples of 25cm² (for algae less than 5cm long), 100 cm² (for algae between 5-10cm long) and whole plants (for algae more than 10cm long) were removed with a spatula from the rocky surface at Caiobá Beach, in August/86, November/86, March/87 and May/87. After sorting, the algal substrata were weighted, their adsorption coefficient calculated and the sediment retained among the thallii weighted. The average distance between the branching was measured for all branched algae. The densities were calculated in relation to the weight of the algal substrate in grams. Eight phytals were considered: Ulva fasciata Delile, Padina gymnospora (Kútzing) Vickers, Sargassum cymosum Garth, Porphyra atropurpurea (Olivi) De Toni, Gelidium sp., Gymnogongrus griffithsiae (Turner) Martius, Pterocladia capillacea (Gmelin) Bornet &Thurel and Pterosiphonia pennata (Roth) Falkenberg, over which nine Amphipoda species live: Ampithoe ramondi Audouin, 1816, Cymadusa filosa Savigny, 1852, Elasmopus pectenicrus Bate, 1857, Hyale media Dana, 1857, Hyale sp.l, Jassa falcata Montagu, 1895 and Sunampithoe pelagica H. Milne-Edwards, 1830 (Gammaridea). Caprella danilevskii Czerniavski, 1861 and Caprella penantis Leach, 1814 (Caprellidea). Amphipoda densities ranged from 0.27 ind.g-1 to 45.68. ind.g-1. The broad-thallii algae Porphyra, Ulva and Padina harbored lower densities of Amphipoda, whereas those finely branched Pterocladia, Pterosiphonia and Gymnogongrus, the highest values and the less branched Sargassum and Gelidium, intermediate values. The high densities found in the finely branched algae had as main contribution the juvenile recruiting of most Amphipoda. The tide level might have influenced the temporal distribution of the Amphipoda density, due to the distinct time of air exposition in eaeh collection data. Most Amphipoda did not show specific algal substratum colonization: only Sunampithoe pelagica occurred solely in Sargassum. Four species occurred in different branched algae: J. falcata. S. pelagica. C. danilevskii and C. penantis. H. media had Sargassum, Pterocladia, Pterosiphonia and Gymnogongrus as the best algal substrata, whereas Caprellidea, the Pterocladia and Pterosiphonia phytals. High sediment weight in Padina was the main reason for high densities of Hyale sp.l in this phytal. The occurrence of males, females (including ovigerous ones) and juveniles of most Amphipoda species found in the present study indicates a complete life cycle whithin these phytals and corroborates with the assumption of the complexity of this marine coastal ecosystem.